Diagnostic delay in wild type transthyretin cardiac amyloidosis – A clinical challenge. (1st April 2020) - Ladefoged, Bertil; Dybro, Anne; Povlsen, Jonas Agerlund; Vase, Henrik; Clemmensen, Tor Skibsted; Poulsen, Steen Hvitfeldt
Abstract: Aim: To determine the diagnostic delay in patients with wild-type transthyretin cardiac amyloiodosis (ATTRwt). To determine the clinical and echocardiogtraphic characteristics of patients with an early and a late diagnosis and to study the suspected diagnoses and identification of diagnostic "red flags" before the ATTRwt diagnosis was established. Methods: In 50 consecutive patients with ATTRwt diagnosed from 2017 to 2019, clinical and echocardiographic patient characteristics were investigated based on electronic patient charts and echocardiographic database review at Aarhus University Hospital, Denmark. Results: The median diagnostic delay was 13 months (2–47 months) and a diagnostic delay above 3 months was associated with more advanced symptoms and left ventricular (LV) diastolic dysfunction at the time of the diagnosis. Thirty patients (60%) were investigated for at least two non-ATTRwt diagnoses during the time period from the first cardiac examination to the time of the confirmed diagnosis. ATTR red flags were significantly less used in patients with the longest diagnostic delay ( p  < 0.001). Abormal LV global longitudinal strain (LV-GLS < 18%) and apical sparring ratio (APSR ≥ 1.5) were present in 96% and 94% of the ATTRwt patients, respectively. Conclusion: The diagnostic delay in ATTRwt was substantial and a prolonged diagnostic delay was associated with more advanced symptoms and LV diastolic dysfunction at the time of the diagnosis. Established ATTR red flags are poorly utilized in the diagnostic process. Echocardiographic analysis of LV-GLS and APSR contributes significantly to the evaluation of LV myocardial performance and helps raise the suspicion of ATTRwt. Highlights: Diagnostic delay among patients with wild-type transthyretin cardiac amyloidosis is significant, median delay is 13 months. Diagnostic tools are widely available and sensitive but are poorly used in everyday clinical practice. Prolonged diagnostic delay was associated with increased NYHA class and diastolic dysfunction.